A novel 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide‐based reactive flame retardant for epoxy resin: Synthesis, properties, and comparison. Issue 8 (24th September 2021) - Xu, Qibin; Zhang, Shengchang; Su, Zexi; Li, Dazhe; Liang, Shuheng; Li, Bo; Lian, Tingting; Qin, Xiangpu; Jiang, Mengjin; Liu, Pengqing
Abstract: 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) and DOPO derivatives had always been regarded as main candidates for improving the flame retardancy of epoxy resin (EP). In this paper, a novel reactive flame retardant DOPOMAH was synthesized from the reaction between DOPO and cis‐butenedioic anhydride (MAH), thereafter acted as a co‐curing agent for EP to remarkably improve the flame retardancy of matrix. The effects of DOPOMAH and DOPO on comprehensive performance of EP were systematically investigated and compared through dynamic mechanical analysis, mechanical performance testing, limiting oxygen index (LOI), vertical burning (UL‐94), and cone calorimetry test. These results indicated that the excellent dispersion of DOPOMAH in EP makes the EP modified by DOPOMAH has good mechanical properties. When the content of phosphorus is 2.0 wt%, compared with the EP modified by DOPO (ED), the LOI of the EP modified by DOPOMAH (EDM) increased from 30.6% to 32.8%, and the UL‐94 was also improved from no rating to V‐0. Meanwhile, the peak heat release rate of EDM was only 51% of that of pure EP, which was slightly less than that of ED. Finally, a flame‐retardant mechanism comparison between DOPOMAH and DOPO was discussed in detail to reveal the reasons why the flame reatardant effect of DOPOMAH was better than that of DOPO. Abstract :